Descrição de uma zona híbrida e mecanismos de isolamento reprodutivo entre duas espécies de caboclinhos (Sporophila Pileata e S. Bouvreuil) (aves: passeriformes) e suas implicações para conservação - Medolago, Cesar Augusto Bronzatto (Universidade Federal de São Carlos, 2018)
Hybridization is often a natural process that plays an important role in the evolutionary process among many species. On the other hand, when human environmental changes cause the phenomenon, it can result in detrimental effects on the species involved, leading to biodiversity loss. Several mechanisms can shape a hybrid zone, keeping it stable, thus avoiding the homogenization of parental taxa and, consequently, the disappearance of one or them both. Understanding the mechanisms that shape the hybrid zones contributes with the knowledge of the evolutionary history and provides subsidies to draw of conservation plans. Several autors have studied hybrid zones in birds, but few have directly accessed nests and relationships between adult individuals. Birds of the genus Sporophila form a conservation interest group due to high number of threatened species. The “capped group” (capuchinos) consists in 12 little species of seedeaters very similar in shape, having their main differentiation in the plumage colour of the adult males. Several species migrate and nest in specific sites and often in sympatry, but the hybridization of species in nature has never been confirmed. This study describes the first hybrid zone between two species of capuchinos. To confirm the presence of hybridization, we studied three areas in State of São Paulo, with reproductive populations of S. pileata and one of which is also a reproductive site of S. bouvreuil. We sequenced 91 adult individuals for the mitochondrial gene COI including individuals with the phenotype of each species, females and individuals with intermediate plumage. The haplotypic distribution varied between the areas and in the contact area between the species all phenotypes presented both haplotypes (SBO), evidencing the hybridization. Through microsatellite markers, we observed the presence of two groups within the SBO population, with 15 potentially pure individuals for S. bouvreuil and 14 for S. pileata. We confirmed the paternity of offspring of two couples, whose individuals had different mtDNA haplotypes and among individuals with q<0.90, showing that hybrid individuals are fertile. Our data confirms the hybrid zone between the the capuchinos and the fertile of hybrid individuals. Although there are no individuals with S. bouvreuil phenotype in the other areas, the presence of individuals with intermediate plumages and mtDNA haplotype of the species indicates an area of gene introgression in the other areas, due to the dispersion of hybrids.
Keywords: Zona hibridização; Evolução; Reprodução isolada; Introgressão; Hybrid zone; Evolution; Reproductive isolation; Introgression; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::GENETICA; CIENCIAS BIOLOGICAS::ZOOLOGIA; CIENCIAS BIOLOGICAS